2013
DOI: 10.1039/c3cs00001j
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent glycoliposomes and micelles to study carbohydrate–protein and carbohydrate–carbohydrate interactions

Abstract: This tutorial review describes multivalent carbohydrate-protein and carbohydrate-carbohydrate interaction studies that utilize self-assembled aggregates of thermodynamically stable liposomes and micelles. Strategies to prepare multivalent glycoliposomes and micelles include: (i) insertion of synthetic glycolipids into matrix lipids; (ii) preparation of glycolipids that aggregate to liposomes and micelles and (iii) modification of the hydrophilic surfaces with desired sugars. Several design strategies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 64 publications
(80 reference statements)
0
85
0
Order By: Relevance
“…Chemical synthesis, purification and characterization of such amphiphilic compounds is a very complex process. [17] Synthesis of new glycosyl lipoconjugates provides many advantages with respect to the design of carbohydrate ligands having specific structural characteristics and their binding on different lipophilic anchors such as fatty acids [31] and cholesterol. [42] In our previous research, we have shown how adamantane can be used as a membrane anchor in lipid bilayer for different carbohydrate molecules which are exposed on liposome surface.…”
Section: Preparation Of Mannosylated Liposomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical synthesis, purification and characterization of such amphiphilic compounds is a very complex process. [17] Synthesis of new glycosyl lipoconjugates provides many advantages with respect to the design of carbohydrate ligands having specific structural characteristics and their binding on different lipophilic anchors such as fatty acids [31] and cholesterol. [42] In our previous research, we have shown how adamantane can be used as a membrane anchor in lipid bilayer for different carbohydrate molecules which are exposed on liposome surface.…”
Section: Preparation Of Mannosylated Liposomesmentioning
confidence: 99%
“…[12,40] The glycosylation as well as mannosylation of liposome surface can be accomplished in several ways. [17] The most used methods encompasses adsorption of different glycopolimers or a chemical reaction between the glycosylconjugate and liposome. [41] Although simple, these methods are constrained regarding the stability of liposomes in the reaction mixture.…”
Section: Preparation Of Mannosylated Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to incorporate the GLs in a lipid monolayer or bilayer, such that the protein-GL interactions can be studied in a more native-like environment [10]. For such studies, a variety of different model membranes have been used to solubilize the GLs, including supported lipid bilayers, liposomes, micelles, bicelles, nanodiscs, and picodiscs [11][12][13][14], and the protein-GL interactions probed using diverse analytical techniques (e.g., fluorescence, nuclear magnetic resonance (NMR), and SPR spectroscopy) [15][16][17][18].between water-soluble lectins and GLs, solubilized using nanodiscs (NDs), have been detected using the catch-andrelease (CaR)-ESI-MS assay [19,20]. Nanodiscs are discoidal phospholipid bilayers surrounded by two copies of an amphipathic membrane scaffold protein [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Mannosylated liposomes have been recognized as promising non-live vectors for targeted delivery purposes. In the past few decades several strategies have been developed to promote an adequate coating of liposomes, used as drug or antigen carrier, with the mannose derivative that specifically recognizes MR receptor (Irache et al, 2008;Jayaraman et al, 2013;Schuster et al, 2003). To study carbohydrate-protein interactions, or the mechanism of lectin action, a variety of methods can be used.…”
Section: Introductionmentioning
confidence: 99%